(3EbJUGOjGJ GdJLGQI GdNGQLjIs - (3MSGe Ydj(B, (3OGhOs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B,s, 2002)
(3GdJLGQI GdNGQLjI(B- (3fXQjGJ GdJLGQI GdNGQLjI(B- (3GdCSGdjH GdfXQjI GdMOjKI aj GdJLGQI GdOhdjI(B- (3GdSjGSGJ GdJLGQjI GdOhdjI(B- (3GdSjGSI GdJLGQjI aj MGdI GdOhdI GdcHjQI heXGgQ aTd GdShb(B- (3eRGjG hYjhH GdMeGjI GdJLGQjI(B- (3GdEJaGbjI GdYGeI ddJYQajI GdLeQcjI hGdJLGQI GdNGQLjI aj GdCQOfs
Keywords: (3EbJUGOjGJ GdJLGQIs; (3GdEbJUGOs; (3GdJLGQI GdNGQLjIs; (3GdJLGQI GdOhdjIs